Green Economy Implementation in the Agriculture Sector Moving from Theory to Practice - Musvoto, Constansia (SpringerBriefs in Agriculture,, 2018)
This book, focusing on the agriculture sector, provides useful analysis of the green economy implementation context and a practical framework for implementing vegetable crop production green economy projects. The book addresses a distinct gap, as there are currently no guidelines available for planning and implementing green economy projects in the agriculture sector. The book combines information from desktop reviews and field research on vegetable production in a green economy context in South Africa in order to bridge the gap between the theoretical green economy concept and practical implementation issues that would be encountered at the project level. It includes a step-by-step process for translating abstract green economy principles into tangible projects on the ground, so that the potential benefits of a green economy are realizable.